The Federal Democratic Republic of Ethiopia : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Federal Democratic Republic of Ethiopia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Federal Democratic Republic of Ethiopia's 2007 Article IV Consultation reports on the macroeconomic imbalances and on maintaining medium-term macroeconomic stability while fostering growth potential. Although agriculture continues to be the mainstay of the economy, the expansion has been broad-based, with manufacturing, construction, and services making significant contributions. Expansion of domestic credit has continued to be brisk, reflecting a pickup in private sector economic activity and increasingly negative real interest rates. A critical challenge for Ethiopia is to strike a judicious balance between demand-dampening measures and growth-enhancing structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet